Komposisi Hasil Tangkapan Longline di Pelabuhan Benoa, Provinsi Bali - Wattimena, Adolf Krisna Mahendra; Dirgayusa, I Gusti Ngurah Putra; Puspitha, Ni Luh Putu Ria (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
Tuna longline fishing was first introduced to the Indonesian people around 1954, pioneered by the Center for Marine Fisheries, and for the first time in 1962, long line tuna fishing was attempted commercially by BPU Fisheries. Fisheries.Longline tuna fisheries in Indonesia, especially in the Indian Ocean, began to develop since the establishment of the state company PT (Persero) Fisheries Samudra Besar in 1972 which is located in Benoa, Bali. Benoa Harbor is the main port in Bali Province and is one of the bases for the distribution of tuna fish in Indonesia apart from Muara Baru (Jakarta), Pelabuhan Ratu (West Java) and Cilacap (Central Java). As one of the main tuna fishing ports, Benoa Harbor is the base for industrial scale tuna fishing vessels operating in the waters of the Indian Ocean.